An Analysis of the Power to Issue Ordinance in India. (18th October 2019) - Bhardwaj, Chandrasekaran Mridul
Abstract: Ordinances making power is one of the most controversial powers that has been vested with executive in India. This power is a substitute of legislative power of the legislature and is meant to be used only in situations comprising of exigencies. However, in practicality this power has often been misused by the executive, and is used to circumvent the legislative process. Due the misuse of this power, it is imperative to examine its history and scope. The power to make ordinance have been a reminiscent of the British rule in India. It was conceptualized through the various Government of India acts, and then post-independence it was adopted under the Indian Constitution. Though the present form of ordinance making power is much more curtailed when compared to the British era, still it leaves ample discretion at the hand of executive to use it erroneously for political gains.